2011
DOI: 10.1111/j.1447-0756.2010.01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of the steroid receptor coactivator family in human ovarian endometriosis

Abstract: The present study demonstrates the expression pattern of SRCs in ovarian endometriosis. It appears that SRC-1 is predominant among the other SRC family members and colocalizes with ERα. Although further study is needed, SRC-1 may affect the transcriptional activity of ERα in human ovarian endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…We observed that there was no cyclic difference in the expression of the three SRCs in ectopic endometrium throughout the whole menstrual period. Our results are similar to the previous immunohistochemical data ( Kumagami et al 2011). The ability of P 4 to inhibit E 2 -induced CXCL12 expression and monocyte chemotaxis was greatly attenuated compared with E 2 stimulation alone when NCOA2 was silenced whether in normal ESCs or in ectopic ESCs, though the CXCL12 expression showed no significant difference between NCOA1 silencing and NCOA2 silencing in ectopic ESCs treated with E 2 CP 4 .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…We observed that there was no cyclic difference in the expression of the three SRCs in ectopic endometrium throughout the whole menstrual period. Our results are similar to the previous immunohistochemical data ( Kumagami et al 2011). The ability of P 4 to inhibit E 2 -induced CXCL12 expression and monocyte chemotaxis was greatly attenuated compared with E 2 stimulation alone when NCOA2 was silenced whether in normal ESCs or in ectopic ESCs, though the CXCL12 expression showed no significant difference between NCOA1 silencing and NCOA2 silencing in ectopic ESCs treated with E 2 CP 4 .…”
Section: Discussionsupporting
confidence: 82%
“…Several researchers have reported the expression of SRCs in normal endometrium, ectopic endometrium, and ovarian endometriotic tissue detected by immunohistochemistry and semi-quantitative RT-PCR (Suzuki et al 2010, Kumagami et al 2011. In this study, the expression patterns and levels of NCOA1, NCOA2, NCOA3, and CXCL12 in normal and ectopic endometrium during the menstrual cycle were characterized using qPCR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endometriosis is an estrogen-dependent condition marked first by ectopic endometrium typically associated with the presence of peritoneal leukocytes and macrophages that overproduce IL1, IL6, TNF and other proinflammatory cytokines and which has been associated with increased risk for endometrial cancers (66). Expression profiling of human ovarian endometriotic tissue showed high overall levels of NCOA1 and ER␤ as well as an increased abundance of NCOA1-and ER␤-stained cells (67,68). More recently, increased levels of ER␣ as well as NCOA1 and NCOA3 in endometriotic tissue have been described (69).…”
Section: Ncoas and Estrogen Receptors (Er␣ And Er␤)mentioning
confidence: 98%